Qualitative analysis of the chemical profile of medicinal plants olegge garden Nova Esperança (Research, Society and Development, 2020)
The present work is about the qualitative analysis of classes of secondary metabolites present in samples of five species of medicinal plants from the garden of Faculdades Nova Esperança, being: Justicia pectoralis Jacq var. stenophylla Leonard, Symphytum officinale L., Dysphania ambrosioides L., Ocimum basilicum L. and Artemisia vulgaris L. seeking to know the profile of secondary metabolites produced by the species by phytochemical screening and 1H NMR. For qualitative analysis, an aliquot of each extract was subjected separately to specific tests, established in the literature, to identify the presence of the following classes of constituents : Flavonoids, Saponins, Alkaloids, Tannins and Terpenoids, as well as by 1H NMR spectra. Thus, comparisons were made with the literature in order to verify the presence of metabolite classes related to biological activities. Our data allowed us to verify the predominance of classes such as: flavonoids, alkaloids and terpenes in the species, combined with the identifications of these classes of compounds through characteristic regions in the 1H NMR spectra allowing us to target a phytochemical profile for each plant separately.